Pengaruh Perendaman Perasan Daun Mimba (Azadirachta indica L.), Mengkudu (Morinda citrifolia L.), Daun Sambiloto (Andrographis paniculata) terhadap Keawetan Tahu - Astuti, Tri; Izzati, Munifatul (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2010)
Tofu is the main protein source of Indonesian food. It is cheap but high quality of nutrition content. This food is usually preserved by toxic chemical, formalin. This experiment observed if natural product may be efficiently used as tofu natural preservation. Several leave extracts has been tested as tofu preservation. These are, mimba (Azadirachta indica L.), mengkudu (Morinda citrifolia L.), and sambiloto (Andrographis paniculata). All of these leave extracts has been known contain antibacterial compound. The aim of this research was to study the efficiency of these three leave extract for tofu preservation. Tofu were soaked at difference concentration of leave extracts of 50%, 25%, and 12,5%. As a result extract mimba is the most effective preservation for tofu. The most effective concentration for tofu preservation of mimba extract was 5%.